2017
DOI: 10.15171/jlms.2018.08
|View full text |Cite
|
Sign up to set email alerts
|

Ablative Fractional 10 600 nm Carbon Dioxide Laser Versus Non-ablative Fractional 1540 nm Erbium-Glass Laser in Egyptian Post-acne Scar patients

Abstract: Introduction: Non-ablative fractional erbium-doped glass 1540 nm and fractional ablative 10600 nm carbon dioxide lasers are regarded as effective modalities for treating acne atrophic scars. In this study, we aimed to compare the effectiveness of fractional CO2 laser and fractional nonablative 1540 nm erbium doped glass laser in treating post acne atrophic scars in Egyptian patients. Methods: Fifty-eight patients complaining of moderate and severe acne atrophic scars were randomly divided into 2 groups of 29 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 13 publications
2
36
0
3
Order By: Relevance
“…The highest GAS scores for the FACL‐treated patients were recorded for patients treated with an interval of > 6 weeks between sessions, which is 2 weeks longer than the 4‐week interval reported by others . The interval between treatment sessions did not significantly influence the results of the other two EBDs.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The highest GAS scores for the FACL‐treated patients were recorded for patients treated with an interval of > 6 weeks between sessions, which is 2 weeks longer than the 4‐week interval reported by others . The interval between treatment sessions did not significantly influence the results of the other two EBDs.…”
Section: Discussionmentioning
confidence: 59%
“…Ong and Bashir carried out a systematic review that compared the different lasers used for treating acne scars, and found that FACL for acne scars led to improvement ranging between 26% and 83%, whereas the range for NAFL was 26–50%. In most of the articles that described the use of FACL, between 1 and 3 treatment sessions were delivered, with an interval of 3–8 weeks (mostly 4 weeks) between sessions . Most of the reports on NAFL described the use of 1–6 treatments with 2‐ to 6‐week intervals between sessions .…”
Section: Discussionmentioning
confidence: 99%
“…Fractional CO 2 laser substantially improves moderate to severe acne scarring and yields superior outcomes when compared with nonablative lasers 20 . The intervening areas of untouched skin begin a rapid process of repair with epidermal stem cell reproduction and repopulation of the ablated columns of tissue with fibroblast‐derived neocollagenogenesis 21 …”
Section: Discussionmentioning
confidence: 99%
“…Nonablative laser therapy has also been shown to be effective in the treatment of acne scars, especially rolling or boxcar scars. When compared against ablative lasers, nonablative lasers offer a quicker recovery time and lower side effect profile 12 . Kim et al conducted a split face study comparing the 1550 nm Er:Glass fractional laser vs CROSS method in the treatment of atrophic acne scars.…”
Section: Discussionmentioning
confidence: 99%